2002
DOI: 10.1177/107424840200700303
|View full text |Cite
|
Sign up to set email alerts
|

HR (Venoruton1000, Paroven, 0-[beta-hydroxyethyl]-rutosides) vs. Daflon 500 in Chronic Venous Disease and Microangiopathy: An Independent Prospective, Controlled, Randomized Trial

Abstract: Venous microangiopathy was improved by the treatment with Venoruton. The comparison with Daflon indicates that HR is comparatively more effective both on microcirculatory parameters and on signs and symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 21 publications
(23 reference statements)
0
14
0
Order By: Relevance
“…Venoruton, a compound that has been widely used in venous disease, has been shown to have a high degree of safety and to be particularly active on edema, swelling, and signs and symptoms of CVI (27)(28)(29)(30)(31). This pilot study indicates the effects of Venoruton in decreasing the number of circulating endothelial cells in venous disease, suggesting new modes of action of this compound.…”
Section: Resultsmentioning
confidence: 99%
“…Venoruton, a compound that has been widely used in venous disease, has been shown to have a high degree of safety and to be particularly active on edema, swelling, and signs and symptoms of CVI (27)(28)(29)(30)(31). This pilot study indicates the effects of Venoruton in decreasing the number of circulating endothelial cells in venous disease, suggesting new modes of action of this compound.…”
Section: Resultsmentioning
confidence: 99%
“…Oxerutin has been shown to have a high degree of safety and to be particularly active on oedema, swelling, and signs and symptoms of CVI. 32,3436…”
Section: Discussionmentioning
confidence: 99%
“…One observational study 62 and four RCTs 24,46,84,86 reported that MPFF was well tolerated. One observational study 59 and three RCTs 71,75,85 reported good compliance with MPFF. Five observational studies 52,53,59,61,81 and two RCTs 85,86 reported no side effects with MPFF use.…”
Section: Adverse Effectsmentioning
confidence: 98%